Visual inspection reliability for composite aircraft structures - Cook, Lawrence (Cranfield University, 2009)
This thesis presents a study of the effects of surface colour, surface finish and dent shape on the visual inspection reliability of 3D surface indentations common in shape to those produced by impact damage to carbon fibre reinforced epoxy laminates. Falling weight (2.5kg) apparatus was used to produce impact damage to non-painted, non-mesh Hexcel AS4/ 8552 carbon fibre reinforced plastic (CFRP) laminates and painted AS4/ 8552 laminates containing bronze mesh and glass fabric lightning strike protection layers. Ø20 mm and Ø87 mm hemispherical tip impacts to painted 17ply and 33ply laminates at varying energy levels typically produced circular shaped, smoothly contoured, rounded sectional profiles with an absence of surface breaking cracks. Sectional profiles through coordinate measuring (CMM) data of the impact dents were described using a set of geometric variables. Identifying relationships between impact energy and the geometric variables allowed the typical sectional profile through impact damage dents from Ø20 mm and Ø87 mm hemispherical tips on 17ply and 33ply painted CFRP laminates to be calculated for energies between 5J to 80J. Calculated sectional profiles typical of impact damage dents to CFRP laminates were reconstructed as simple revolved shapes using 3D computer aided design (CAD) models. The 3D CAD models were computer numerical control (CNC) machined into 3mm Plexiglas panels to produce facsimiles of hemispherical impact damage dents on CFRP laminates. Facsimile specimen sets of sixteen 600 mm x 600 mm panels were produced in gloss and matt grey, white and blue finishes. Each set contained the same 32 different sized machined dents representing Ø20 mm and Ø87 mm hemispherical tip impact damage to 17ply & 33ply painted CFRP laminate. Each facsimile specimen set was combined with similarly finished unflawed (dent free) panels. 64 panels in each colour/ finish were presented for 5 seconds in a randomised order to a minimum of 15 novice participants in a visual inspection task lasting approximately 25 minutes. II A set of corresponding visual inspection experiments were performed in which physical specimens were replaced by digitally projected actual size photorealistic images of the machining CAD data. Comparisons between the results of the physical and virtual specimen trials revealed differences in detectability for similarly sized dents. The detection results obtained from visual inspection of physical specimens demonstrated that the detectability of dents similar to those caused by higher (>40J) energy impacts from a Ø87 mm hemispherical tip was less than that of the dents caused by lower energy (<20J) impacts from Ø20 mm tips. However, larger subsurface delamination area was demonstrated by the higher energy Ø87 mm impacts than lower energy Ø20 mm impacts on 150 mm x 100 mm coupons of the same thickness laminate. The results of these experiments imply that detectability of dents caused by larger diameter objects at higher energies cannot be assumed to be greater than that of lower energy impacts from smaller diameter objects. The detection results demonstrate that detectability by visual inspection cannot be assumed the same for an impact dent on different surface colours and finishes. In general terms, the highest numbers of dents returning >90% detection were observed on grey specimens and the highest number of dents returning 0% detection were observed on matt blue specimens. The difference in detection rates for similarly sized dents on a gloss and matt finish was least on grey coloured specimens and greatest on blue coloured specimens.